2017
DOI: 10.3390/lubricants5020015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Mechanical Impact of Nanoparticles and pH Effect of the Slurry on the CMP of the Selective Layer Surfaces

Abstract: This paper provides a tribochemical study of the selective layer surface by chemical mechanical planarization (CMP). CMP is used to remove excess material obtained in the process of selective transfer. The paper aims at a better understanding of the planarization (polishing) and micromachining. The planarization becomes effective if the material removal rate (MRR) is optimal and the surface defects are minimal. The pH of the slurry plays a very important role in removing the selective layer by CMP, and hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Slurry consists in its premixed form of 3.0 wt.% fumed colloidal silica particles with a median particle diameter of 250 nm, and a citric acid which is commonly used in metallic selective layer CMP slurries as a buffering or complexing agent [5,6]. H 2 O 2 was added to the premixed slurry to oxidize the selective layer (copper from the selective layer) and enhance its removal.…”
Section: Methodsmentioning
confidence: 99%
“…Slurry consists in its premixed form of 3.0 wt.% fumed colloidal silica particles with a median particle diameter of 250 nm, and a citric acid which is commonly used in metallic selective layer CMP slurries as a buffering or complexing agent [5,6]. H 2 O 2 was added to the premixed slurry to oxidize the selective layer (copper from the selective layer) and enhance its removal.…”
Section: Methodsmentioning
confidence: 99%
“…Effect of slurry pH on rms surface roughness of CZT wafer.-The degree of oxidation by chemical species (oxidizer) in the CMP process is governed by the pH environment of the slurry. 21 Thus, acidic, neutral and alkaline pH values (2.5, 7 and 9) were used in this study to find a suitable pH environment to achieve atomically smooth CZT surfaces. It is well known that pH of the medium has significant influence on the surface charge (zeta potential) and hydrodynamic size of the dispersed silica nanoparticle which govern the stability of the dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…During CMP in general, the three-body contact between abrasive NPs, pad asperities and the wafer surface can result in NPs rolling, or sticking and slipping on the wafer surface. 20 This stick and slip results in the generation of mechanical forces which can be measured through COF. 21 When studying the tribology of CMP, stick-slip refers to a cyclic fluctuation in the magnitudes of frictional force and relative velocity between the wafer and the pad.…”
Section: Resultsmentioning
confidence: 99%
“…21 Previous work has shown that this stick-slip phenomenon creates scratches on the polished wafer surface at lower values of [NP]. 20,21 However, as [NP] increases, pitting deformations of the wafer surface occur faster than scratches, indicating that there is likely more rolling of the NPs than sticking and slipping. 20,21 This is because there is a significant reduction of the load on the individual NPs as their concentration increases.…”
Section: Resultsmentioning
confidence: 99%